Rainfall variability and sowing window effects on maize genotype performance in Chamarajanagara district, Karnataka - Rajath, H P; Kumar, C; Inamdar, S R; Hanumanthappa, M; Bhanuprakash, H R; Vishwanth, V E; Kumar, C V; Manjunath, K; Navinkumar; Kumar, G V S (Plant Science Today, 2026)
The study explores the use of rainfall patterns and maize types in Chamarajanagara district, Karnataka, India, where rainfall varies significantly from place to place and year to year. The researchers used data from weather stations collected every month from January to December 2021 and tested 6 methods to create full maps: Inverse distance weighted (IDW), Spline, Natural neighbour, Trend, Kriging and Topo to Raster. The results show that weather plays a significant role in maize yields, with timing and amount playing a crucial role. Sowing windows or the best weeks to plant seeds, are crucial in this region, as planting too early or too late can lead to water stress. The hybrid MAH 14-5 genotype was found to be particularly effective when sown in the first week of July, resulting in stronger growth, higher nutrition levels and reduced anti-nutritional factors. These findings emphasise the importance of selecting the right planting time to maximise water use efficiency, harness soil conditions and utilise sunlight intensity. Farmers who match sowing to rain peaks can boost yields without extra inputs. The study also highlighted how rain changes over time and space in the district, with some spots experiencing steady showers in June and others experiencing heavy bursts in August, leading to uneven crop growth. Smart planning involves tailoring sowing windows to local rain forecasts, choosing genotypes that fit the area's weather and aligning tasks like fertilising or weeding with rainfall. These steps help farmers adapt and achieve reliable harvests year after year.